Examining the Adequate Content of Antenatal Care for Empowered Women in Nepal - Shrestha, Bidhya (International Research Journal of MMC, 2022)
The most crucial aspects whenever we discuss antenatal care services are the coverage of antenatal care contacts and the contents of antenatal care during pregnancy. During the ANC contact, women get counselling and medical check-upfor their pregnancy which preventsnot only women but also the newborn babiesfrom preventable death. It is a window of opportunity for offering preventive measure to save the mother and newborn’s life. But despite the significance of antenatal care content in Nepal, many women are still being left behind, either directly or indirectly. Women empowerment and adequate content of care during ANC visits are both concerns about women's reproductive rights. Women who have greater power usually use antenatal care facilities. In this regard, the goal of this study is to look into the relationship between women empowerment and adequate content of care. This study is completely based on Nepal Demographic Health Survey, 2016. The main target populations of this study were women who weree currently married and had had at least one child in the two years before the survey. The content of care was found to be inadequate. Thus, women who had been left behind should be empowered to increase the adequate use of ANC services. Likewise, policies and activities should be tailored to serve the most marginalized, poor and vulnerable populations to offer sufficient, timely, and adequate ANC services in Nepal.